Analyzing Genre Patterns in Virtual-Themed Animated Films Using Association Rule Mining - Satrya Fajri Pratama; Eko Priyanto (International Journal Research on Metaverse, 2024)
This study investigates patterns in virtual-themed animated films using association rule mining to explore the relationships between genre combinations, production companies, and their impact on both popularity and revenue. The dataset consists of films from various genres, with a focus on those exploring virtual worlds, alternate realities, and futuristic settings, aligning with metaverse concepts. The analysis revealed several significant findings. The association rule mining results identified that films combining Fantasy and Science Fiction genres are 1.8 times more likely to achieve high box office revenue, with a confidence level of 80%. Additionally, Pixar adventure films were found to have a 2.1 times higher likelihood of attaining high popularity. Films blending Fantasy and Adventure genres showed a strong correlation with high revenue, with a 70% confidence level and a lift value of 1.9. These patterns suggest that imaginative storytelling and virtual world elements are key drivers of success in animated films. Revenue analysis demonstrated that 30% of the virtual-themed films in the dataset generated more than 1 billion USD, while 50% earned between 0.5 and 1 billion USD. The popularity analysis further highlighted that Fantasy, Science Fiction, and Adventure genres consistently rank highest in audience engagement. These findings underscore the significant commercial potential of films exploring virtual and digital environments, particularly as audience demand for immersive experiences continues to grow. This study concludes that films featuring virtual world themes, particularly those combining Fantasy, Science Fiction, and Adventure genres, are well-positioned to succeed both financially and in terms of audience engagement. As AR, VR, and metaverse technologies advance, the demand for immersive cinematic experiences is likely to increase, offering filmmakers new opportunities to innovate and expand this genre.